SISTEM PENUNJANG KEPUTUSAN KESEHATAN UNTUK HIPERTENSI MENGGUNAKAN ALGORITMA C4.5 - Amalia, Hilda; Evicienna, Evicienna (Jurnal Pilar Nusa Mandiri, 2013)
Hypertension is a cardiovascular disease that causes 4.5% of the global disease burden. Hypertension is a major risk factor for heart problems and can be said as the "silent killer" because there are no specific signs and can cause serious illness if left untreated for a long time. Decision support system for hypertension can be used to obtain the results of the decision of the cases, one of them using the decision tree method. Hypertension data will be processed using the method of decision tree algorithm C4.5 through software RapidMiner and will result in a decision support rules, the value of accuracy, and AUC than the rule. After testing the accuracy of the values obtained on the C4.5 algorithm by 76.6%, AUC values for 0862 with a good level of diagnostic classification.